Metastatic colon adenocarcinoma to the gingiva treated with spatial fractionation radiotherapy: a case report - Liu, Xinyi; Xu, Ke; Yao, Quan; Fang, Jian; Zhou, Weiyi; Lang, Jinyi (Frontiers in Oncology, 2025)
Metastatic colon adenocarcinoma to the gingiva is exceedingly rare, accounting for 1–3% of maxillofacial malignancies and usually associated with advanced disease and poor prognosis. This case report describes a 68-year-old woman diagnosed with metastatic colon adenocarcinoma presenting with a metastatic lesion measuring 5 × 3 cm located in the left maxilla. The patient received hybrid spatial fractionation radiotherapy (SFRT) combining stereotactic body radiotherapy (SBRT) with conventional SFRT protocols. Post-radiotherapy, the lesion regressed significantly, bleeding ceased, and oral function improved. However, the patient passed away less than two months after the radiotherapy, due to the high systemic tumor burden and severe disease progression. This case highlights SFRT’s efficacy in local symptom control for rare gingival metastases, despite systemic progression. This report underscores the need for optimized SFRT protocols and multidisciplinary approaches in managing metastatic colorectal cancer.